THE IMPACT OF SUGGESTOPEDIA ON LANGUAGE ACQUISITION - Shahina Shukhratova (Bright Mind Publishing, 2025)
This article explores the impact of Suggestopedia, a language teaching methodology developed by Georgi Lozanov, on language acquisition. By examining its key methodological aspects, this study highlights how Suggestopedia facilitates learning through a relaxed environment, the use of music and art, and the engagement of the learner's subconscious. The findings suggest that Suggestopedia can significantly enhance language acquisition, particularly in terms of retention, fluency, and overall learner satisfaction. This research contributes to the growing body of literature advocating for innovative teaching methodologies that prioritize psychological well-being in educational settings.
Keywords: Suggestopedia, language acquisition, teaching methodology, subconscious learning, educational psychology.